Application of Amino Acids in the Structural Modification of Natural Products: A Review - Xu, Qian; Deng, Hao; Li, Xiaoting; Quan, Zhe-Shan (Frontiers in Chemistry, 2021)
Natural products and their derivatives are important sources for drug discovery; however, they usually have poor solubility and low activity and require structural modification. Amino acids are highly soluble in water and have a wide range of activities. The introduction of amino acids into natural products is expected to improve the performance of these products and minimize their adverse effects. Therefore, this review summarizes the application of amino acids in the structural modification of natural products and provides a theoretical basis for the structural modification of natural products in the future. The articles were divided into six types based on the backbone structures of the natural products, and the related applications of amino acids in the structural modification of natural products were discussed in detail.